Cultural Discourse Study of Media Environmental Communication: A Case Analysis of the Coverage of Chinese Documentary of Haze in American Main Stream Medias - Qiuyang, Li (Sinología hispánica. China Studies Review, 2017)
Frame upon the Cultural Discourse Studies, the present paper focuses on the news discourse about Chai Jing’s documentary “Under the Dome” in American mainstream media, investigating the discourse topic, manner and rhetoric as well as the historical, environmental development and cultural reasons between these two countries. It is found that (1) the Chinese environmental discourse in American mainstream medias concerns the topics likes the popularization of environmental conception, the environmental ineffectiveness of government administration, and the Chinese public’s right to environmental problems; (2) the discourse manners like choice of lexicon, speech quotation, and rhetorical feature applied in American mainstream media has presented the communicative values and conceptions of western country; (3) the Chinese environmental discourse in American media is related with the historical and cultural difference between the two countries.